A Plesiohedral Cellular Network of Graphene Bubbles for Ultralight, Strong, and Superelastic Materials - Yeo, Seon Ju; Oh, Min Jun; Jun, Hyun Min; Lee, Minhwan; Bae, Jung Gun; Kim, Yeseul; Park, Kyung Jin; Lee, Seungwoo; Lee, Daeyeon; Weon, Byung Mook; Lee, Won Bo; Kwon, Seok Joon; et al. (WILEY-V C H VERLAG GMBH, 2018)
Advanced materials with low density and high strength impose transformative impacts in the construction, aerospace, and automobile industries. These materials can be realized by assembling well-designed modular building units (BUs) into interconnected structures. This study uses a hierarchical design strategy to demonstrate a new class of carbon-based, ultralight, strong, and even superelastic closed-cellular network structures. Here, the BUs are prepared by a multiscale design approach starting from the controlled synthesis of functionalized graphene oxide nanosheets at the molecular- and nanoscale, leading to the microfluidic fabrication of spherical solid-shelled bubbles at the microscale. Then, bubbles are strategically assembled into centimeter-scale 3D structures. Subsequently, these structures are transformed into self-interconnected and structurally reinforced closed-cellular network structures with plesiohedral cellular units through post-treatment, resulting in the generation of 3D graphene lattices with rhombic dodecahedral honeycomb structure at the centimeter-scale. The 3D graphene suprastructure concurrently exhibits the Young's modulus above 300 kPa while retaining a light density of 7.7 mg cm(-3) and sustaining the elasticity against up to 87% of the compressive strain benefiting from efficient stress dissipation through the complete space-filling closed-cellular network. The method of fabricating the 3D graphene closed-cellular structure opens a new pathway for designing lightweight, strong, and superelastic materials.
Keywords: MECHANICAL METAMATERIALS; HIGHLY EFFICIENT; LIGHTWEIGHT; AEROGELS; OXIDE; RESISTANT